2003
DOI: 10.1074/jbc.m209732200
|View full text |Cite
|
Sign up to set email alerts
|

The Hepatitis C Virus NS2 Protein Is an Inhibitor of CIDE-B-induced Apoptosis

Abstract: Chronic hepatitis C virus (HCV) infection frequently leads to liver cancer. To determine the viral factor(s)potentially involved in viral persistence, we focused our work on NS2, a viral protein of unknown function. To assign a role for NS2, we searched for cellular proteins that interact with NS2. Performing a two-hybrid screen on a human liver cDNA library, we found that NS2 interacted with the liver-specific pro-apoptotic CIDE-B protein. Binding specificity of NS2 for CIDE-B was confirmed by cell-free assay… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
88
2
2

Year Published

2005
2005
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 106 publications
(95 citation statements)
references
References 55 publications
3
88
2
2
Order By: Relevance
“…In the initial cloning report for CIDEA and CIDEB, it was indicated that apoptosis induced by transient expression of CIDEA in 293T cells was caspase independent due to the failure of caspase inhibitor, when added at 8 h posttransfection, to block CIDEA-mediated apoptosis (11). On the other hand, a study of CIDEB supported a caspase-dependent mechanism of action in that activity of caspase-3, and release of mitochondrial cytochrome c occurred upon transient expression of CIDEB in COS cells (8). It remains to be determined whether the apoptotic mechanism of CIDEA differs from that for FSP27 and CIDEB or whether the early report of caspase independence for CIDEA might be due to the rather late timing of addition of caspase inhibitor in that study (11).…”
Section: Ajp-endocrinol Metabmentioning
confidence: 98%
See 4 more Smart Citations
“…In the initial cloning report for CIDEA and CIDEB, it was indicated that apoptosis induced by transient expression of CIDEA in 293T cells was caspase independent due to the failure of caspase inhibitor, when added at 8 h posttransfection, to block CIDEA-mediated apoptosis (11). On the other hand, a study of CIDEB supported a caspase-dependent mechanism of action in that activity of caspase-3, and release of mitochondrial cytochrome c occurred upon transient expression of CIDEB in COS cells (8). It remains to be determined whether the apoptotic mechanism of CIDEA differs from that for FSP27 and CIDEB or whether the early report of caspase independence for CIDEA might be due to the rather late timing of addition of caspase inhibitor in that study (11).…”
Section: Ajp-endocrinol Metabmentioning
confidence: 98%
“…Studies to date indicate that protein-protein interactions are important to CIDE protein function, and both CIDEA and CIDEB have been studied somewhat in this regard. Homo-and heterodimeric interaction of CIDEA and/or CIDEB (i.e., CIDEA:CIDEA, CIDEB:CIDEB, and CIDEA:CIDEB) has been reported (5,8,11,19,27). CIDEB interacts with viral protein NS2 (8) and apolipoprotein B (42) and CIDEA with AMPK (27); such interactions appear to impact the physiological function of these CIDE partner proteins.…”
Section: Ajp-endocrinol Metabmentioning
confidence: 99%
See 3 more Smart Citations